When Will Stakeholder Groups Act? An Interest- and Identity-Based Model of Stakeholder Group Mobilization - Rowley, Timothy I.; Moldoveanu, Mihnea (Academy of Management Review, 2003)
Timothy J. Rowley, Mihnea Moldoveanu, When Will Stakeholder Groups Act? An Interest- and Identity-Based Model of Stakeholder Group Mobilization, The Academy of Management Review, Vol. 28, No. 2 (Apr., 2003), pp. 204-219